The Ferro-Power MOSFET: Enhancing Short-Circuit Robustness in Power Switches With a Ferroelectric Gate Stack - Marco Boccarossa; Luca Maresca; Alessandro Borghese; Michele Riccio; Giovanni Breglio; Andrea Irace; Giovanni A. Salvatore (IEEE Access)
Power Metal Oxide Semiconductor Field Effect Transistors (MOSFETs) are essential in modern electronics, enabling efficient power conversion and control in a wide range of applications. Wide bandgap semiconductors such as silicon carbide (SiC) and gallium nitride (GaN) have been shown to boost device performance, by providing higher efficiency and faster switching for high-power, high-frequency applications. Although optimised for standard operation, their performance under short circuit (SC) events remains critical mostly because of the higher current density. Notably, SiC MOSFETs can only withstand SC conditions for a few microseconds, necessitating larger layouts or faster control electronics to prevent the catastrophic failure of the device. This paper introduces a novel power device, the Ferro-Power MOSFET, that integrates a ferroelectric material into the gate stack of a power SiC MOSFET. This innovative approach leverages the temperature-dependent dielectric constant of ferroelectrics to effectively reduce the temperature rise during short-circuit events without altering the basic layout of the device neither the control electronics. TCAD simulations and design optimisation of a 1.2 kV SiC MOSFET reveal substantial enhancements, achieving temperature and current reductions of up to 31% and 42%, respectively, without compromising current conduction during normal operation. It stands to reason that this concept is general and can be broadly applied to any power MOSFET. Moreover, it is bolstered by recent achievements in ferroelectricity in CMOS-compatible hafnium oxide (HfO2), thus prospecting concrete experimental developments in power semiconductors.